Kualitas Hidup Pasien Diabetes Melitus Tipe 2 di RS “X” Kabupaten Tanah Bumbu - Alpia Damayanti; Nur Mahdi; Andi Sultang (Universitas Borneo Lestari, 2023)
Diabetes mellitus is a disease with the highest proportion in developing countries. Poor quality of life can affect the disease. This study aims to analyze the quality of life based on the characteristics of type 2 DM patients at one of the Tanah Bumbu district hospitals. The research method used was a quantitative method using a cross-sectional design with convenience sampling technique and using a DQOL questionnaire based on patient characteristics, namely age, sex, education, occupation, marital status and length of illness. This study used Chi Square statistical software analysis with a significance level of p value > 0.05. The data sample is 84 respondents. The results of this study showed that the quality of life of DM patients was in the high category as much as 79.8%, 16.7% in the medium category and 3.6% in the low category. Based on the results of this study where the p value > 0.05 on quality of life based on patient characteristics there is no significant relationship between characteristics and quality of life.